Principales insectos plagas en el cultivo de aguacate (Persea americana L.) en el Ecuador - Cano Morejón, Deniss Jamilet (2023)
The avocado is a fleshy exotic fruit obtained from the tropical tree of the same name. In some parts of South America, it is known as Palta or avocado. Avocado cultivation occurs in more than 60 countries, Mexico stands out as the main producing country. According to INEC data, 7,195 hectares in Ecuador are dedicated to growing avocado in the provinces where avocado is produced are Carchi (36%), Pichincha (31%), Imbabura (18%), Tungurahua (8%) and Santa Elena (7%) on the coast. There are several problems present in the commercial production of avocado in Ecuador, among them the attack of pests, which reduces the quality and quantity of fruits. Some authors indicate that between 15 - 25% of producers cite problems of this type, the presence of pests in the harvested product is one of the main limitations in the admissibility of fruits. The objective of the work was to characterize the main insect pests in avocado cultivation in Ecuador. In this sense, information was collected from relevant bibliographic sources to determine the situation raised above. After reviewing the documents, the presence of a constant group of pest insects in the avocado crop is visible. These pests are mainly found in the mountain region, due to the presence of more technical commercial plantations, the vast majority of which are monoculture or with little association of species. This generates a prevalence of inocula for the manifestation of insects. The study also shows a participation of defoliating insects, these attack to a lesser extent, but remain a problem especially in the architecture of the tree. However, the decrease in leaf area is linked to the photosynthesis of the plants, a lower leaf area would affect the formation of chlorophyll, so the formation of photosynthates would fall, causing a loss in the size of the fruits. The pests with the greatest presence in commercial avocado plantations in Ecuador are: Red Spider, Seed Borer, Thrips, Mealybugs, Aphids, Basket Worm, Green Fly and Fruit Fly